Environmental exposures as risk factors for idiopathic inflammatory myopathies - Opinc-Rosiak, Aleksandra H.; Makowska, Joanna S. (Journal of autoimmunity, 2023)
Idiopathic inflammatory myopathies (IIM) are a heterogeneous group of rare autoimmune diseases, with increasing incidence rates observed in the recent years. The pathogenesis of IIM remains not fully understood, and the interaction of genetic and environmental factors is suspected. It is unclear whether the observed upward trend in the IIM incidence is solely due to improved access to effective diagnostics or perhaps due to increased exposure to external risk factors. The PUBMED database was thoroughly searched for articles describing environmental exposures potentially triggering the onset of IIM. The article summarizes the current knowledge available on this subject, taking into account various environmental factors, including among others UV radiation, infectious agents with SARS-CoV-2, inhaled particles, or iatrogenic effects. Limitations and unmet needs requiring further studies were highlighted. [Display omitted] •Environmental exposures serve a significant role in the pathogenesis of IIM•Seasonal variability of IIM incidence supports the idea of environmental triggers•Exposure to UV radiation is associated with the risk for IIM in susceptible ones•Preceding infections are considered as one of the strongest risk factors for IIM•Impact differs depending on IIM subtype, demographical data and serological profile